Effects of Hallux Valgus Orthoses on Ground Reaction Force Using 3D Motion Analysis in Individuals With Hallux Valgus Deformity - Yong-wook Kim (Korean Research Society of Physical Therapy, 2020)
Background: Hallux valgus (HV) is a foot deformity developed by mediolateral deviation of the first metatarsophalangeal joint. Although various foot-toe orthoses were used to correct the HV angle, verification of the effects of kinetics variables such as ground reaction force (GRF) through three-dimensional (3D) gait analysis according to the various type of orthoses for HV is insufficient. Objects: This study aimed to investigate the effect of soft and hard types of foot and toe orthoses to correct HV deformity on the GRF in individuals with HV using 3D motion analysis system during walking. Methods: Twenty-six subjects participated in the experiment. Participants had HV angle of more than 15° in both feet. Two force platforms were used to obtain 3D GRF data for both feet and a 3D motion capture system with six infrared cameras was used to measure exact stance phase point such as heel strike or toe off period. Total walk trials of each participant were 8 to 10, the walkway length was 6 m. Two-way repeated measures ANOVA was used to determine the effects of each orthosis condition on the various GRF values. Results: The late anteroposterior maximal force and a first vertical peak force of the GRF showed that the hard type orthosis condition significantly increased GRF compared to the other orthosis conditions (p < 0.05). Conclusion: There were significant effects in GRF values when wearing the hard type foot orthosis. However, the hard type foot orthosis was uncomfortable to wear during walking. Therefore, it is necessary to develop a new foot-toe orthosis that can compensate for these disadvantages.